1990
DOI: 10.1111/j.1600-0447.1990.tb05479.x
|View full text |Cite
|
Sign up to set email alerts
|

Female alcoholics. II. The expression of alcoholism in relation to gender and age

Abstract: A sample of 233 consecutive alcohol-dependent female admissions were cross-matched for date of birth and admission with male subjects of similar ethnic background. Primary drug abusers were not included. A quarter of subjects of both sexes were married. There were no gender or age differences in the level of family history of alcoholism. Highly significant gender and age differences were found in alcohol-related behaviours, which were more prominent in the younger age groups and in male subjects. These crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
7
1
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
(6 reference statements)
6
7
1
1
Order By: Relevance
“…It is widely accepted that in alcoholic adult populations, males drink more than females, yet females show 'telescoped' development of alcohol-related problems (defined by a faster progression to dependence and more physical problems as a result of alcohol use) (Blankfield, 1990;Piazza et al, 1989;Randall et al, 1999). Recently, investigators and clinicians have focused on gender differences in adolescents with SUD, and the results are generally in agreement with those of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…It is widely accepted that in alcoholic adult populations, males drink more than females, yet females show 'telescoped' development of alcohol-related problems (defined by a faster progression to dependence and more physical problems as a result of alcohol use) (Blankfield, 1990;Piazza et al, 1989;Randall et al, 1999). Recently, investigators and clinicians have focused on gender differences in adolescents with SUD, and the results are generally in agreement with those of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Skinner found that the unfavourable consequences of drinking correlated more strongly with the reported amounts of alcohol consumed (r = 0.58) rather than the number of years spent drinking (r = 0.33) (5,6). The present study confirmed a definite relationship between MAST scores and the reported daily amount of alcohol intake (19).…”
Section: Mast Score and Alcohol Intakesupporting
confidence: 79%
“…An epidemiological community survey has confirmed the constrained social behaviour in unidentified elderly male alcoholics (29). Less disruptive social behaviours have been described in female (17,19,25) and elderly (19,29,30) alcoholics and other possible areas of exploration have been suggested (17,30).…”
Section: Diagnostic Difficulties and Alcoholismmentioning
confidence: 80%
See 2 more Smart Citations